Husserl and Heidegger on Modernity and the Perils of Sign Use - Johan Blomberg (Philosophies, 2022)
In his late writings Husserl emphasizes how the semiotic properties of writing, and of mathematical formulae and diagrams, are crucial for the historical, cross-generational survivability of meaning and specifically indispensable to the operation of scientific knowledge. However, the demand for objectivity, exactitude, and repeatability insidiously interferes with the meaning that such signs seek to express. This leads to a duality of objectivity encapsulated in the notion “the sedimentation of meaning”. On this view, the transmission of objectivity established in an original sense-constituting act cannot survive unless being deposited in some external form, which at the same time risks the original sense being irrevocably lost in a web of signification that amounts to nothing more than empty and meaningless symbol manipulation. I discuss Husserl’s analysis and propose that it is limited by its one-sided focus on the negative impact of modernity. I compare Husserl’s account with Heidegger’s even more radical critique of modern society as one where a so-called “technological” mode of “revealing” reigns supreme at the expense of eradicating other, and more authentic ways to apprehend the world. I critically reconstruct the respective position of both thinkers and show how they point not only to a criticism of the instrumentalization and formalization of knowledge in modern society, but that they are just as importantly highlighting essential semiotic properties of signs.